Recent progress on operator theory and approximation in spaces of analytic functions : Conference on Completeness Problems, Carleson Measures, and Spaces of Analytic Functions, June 29-July 3, 2015, Institut Mittag-Leffler, Djursholm, Sweden - Completeness Problems, Carleson Measures, and Spaces of Analytic Functions (Conference); Bénéteau, Catherine; Condori, Alberto A.; Liaw, Constanze; Ross, William T.; Sola, Alan A. (Contemporary mathematics, 2016)
This volume contains the Proceedings of the Conference on Completeness Problems, Carleson Measures, and Spaces of Analytic Functions, held from June 29-July 3, 2015, at the Institut Mittag-Leffler, Djursholm, Sweden.The conference brought together experienced researchers and promising young mathematicians from many countries to discuss recent progress made in function theory, model spaces, completeness problems, and Carleson measures.This volume contains articles covering cutting-edge research questions, as well as longer survey papers and a report on the problem session that contains a collection of attractive open problems in complex and harmonic analysis.